Role of mechanical alloying parameters on powders distribution of Al/Cu alloy and Al/Cu composite - Jamal, N. A.; Farazila, Y.; Ramesh, S.; Anuar, Hazleen (W. S. Maney & Son Ltd, 2014)
The aim of the current study is to investigate the effect of milling time and speed on mixing properties of aluminium (Al)/copper (Cu) alloy and Al/Cu composite. Ethanol and argon gas were employed as process control agent and milling atmosphere. Mechanical alloying process by means of high-energy ball milling was performed to produce alloy and composite metal powder. This process proceeds through repeated deformation, cold welding and fracturing of powder particles mixture with a controlled fine microstructure. X-ray diffraction and particle size analyser confirmed particle size reduction of Al/Cu alloy with increasing milling time and speed. On the other hand, the addition of reinforcement particles was found to accelerate the milling process of Al/Cu composite. Scanning electron microscope micrographs revealed homogeneous distribution of powder mixture particles by mechanical alloying process at changing milling conditions.